Uma metacompreensão da investigação matemática nas produções do Programa de Desenvolvimento Educacional do Paraná PDE - Wichnoski, Paulo (2016)
In this thesis we have entered into meta understanding the manifests of Mathematics Research in productions of teachers who worked from this perspective PDE - Educational Development Program of the Paraná State. We analyze what is manifested on the Mathematics Research in teacher education mathematics teaching in the context of a public policy of teacher training. For this, we carried out this research, guided by the following question: What does it show Mathematics Research in productions of teachers who worked from the perspective of Mathematics Research on PDE - Educational Development Program of Paraná? The methodological approach taken is qualitative in the phenomenological attitude research with hermeneutic graft. The material analyzed is related to sixty-eight productions, divided between teaching units and articles, produced under the EDP in 2007, 2008, 2009, 2010 and 2012. After a phenomenological exercise emerged three categories, namely 1) the ways of understanding mathematics research, 2) so that the mathematics Research enters into the classroom, and 3) the dialogue of mathematics Research with other trends in the teaching of mathematics. Analyze them in light of our research question, searching for what is shown in the structure of the investigated phenomenon, transcending first impressions. Interpretations made allow us to state that the understanding of Mathematics Research is revealed impregnated knowledge that the teacher brings from the context in which it appears, marked by cultural, social and historical factors. Theoretically, it shows itself open to dialogue with the History of Mathematics, Technology Media and, significantly, with Troubleshooting. Turns out a speech on the Mathematics Research on practical work with this trend and the possibilities of dialogue with other trends by the PDE teachers, however, when entering the classroom environment it is not effective. This points to the creation of educational processes that address the practical and theoretical dimension as opposed to the unilateral model theory → practice, entered in the classroom context, that, as the teacher 'is formed' can also 'form their students' in a constant process of learning Mathematics Research collectively, overcoming a purely intellectualized model and technical rationality.